Cardiac sarcoidosis: modern diagnostics and therapy - V. V. Shabalin; Yu. I. Grinshteyn (Российский кардиологический журнал)
Cardiac sarcoidosis (CS) is a potentially life-threatening granulomatous heart disease with unclear etiology and a suspected pathological immune response to an unidentified antigenic trigger in individuals with a genetic predisposition. CS often occurs as a part of systemic sarcoidosis, but in rare cases it can be isolated. The latter phenotype is especially difficult to diagnose, since it requires a differential diagnosis with a number of other myocardial diseases. Depending on the location and area, the clinical performance can vary from asymptomatic to severe cardiac manifestations — decompensated heart failure, malignant arrhythmias and conduction disorders, as well as sudden death. Methods for diagnosing CS are constantly being improved. In the presented review, the emphasis is on modern methods, diagnostic criteria, and approaches to the therapy of CS.